CHILES VI: H i and H α observations for z < 0.1 galaxies; probing H i spin alignment with filaments in the cosmic web. Issue 1 (3rd December 2019) - Blue Bird, J; Davis, J; Luber, N; van Gorkom, J H; Wilcots, E; Pisano, D J; Gim, H B; Momjian, E; Fernandez, X; Hess, K M; Lucero, D; Dodson, R; et al.
ABSTRACT: We present neutral hydrogen (H i ) and ionized hydrogen (H α) observations of 10 galaxies out to a redshift of 0.1. The H i observations are from the first epoch (178 h) of the COSMOS H i Large Extragalactic Survey (CHILES). Our sample is H i biased and consists of 10 late-type galaxies with H i masses that range from 1.8 × 10 7 M⊙ to 1.1 × 10 10 M⊙ . We find that although the majority of galaxies show irregularities in the morphology and kinematics, they generally follow the scaling relations found in larger samples. We find that the H i and H α velocities reach the flat part of the rotation curve. We identify the large-scale structure in the nearby CHILES volume using DisPerSE with the spectroscopic catalogue from SDSS. We explore the gaseous properties of the galaxies as a function of location in the cosmic web. We also compare the angular momentum vector (spin) of the galaxies to the orientation of the nearest cosmic web filament. Our results show that galaxy spins tend to be aligned with cosmic web filaments and show a hint of a transition mass associated with the spin angle alignment.